2018
DOI: 10.1186/s12870-018-1553-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ploidy variation on promoter DNA methylation and gene expression in rice (Oryza sativa L.)

Abstract: BackgroundPolyploidy, or whole-genome duplication (WGD) promotes genetic diversification in plants. However, whether WGD is accompanied by epigenetic regulation especially DNA methylation remains yet elusive. Methylation of different region in genomic DNA play discrete role in gene regulation and developmental processes in plants.ResultsIn our study, we used an apomictic rice line (SARII-628) that produces twin seedlings of different ploidy for methylated DNA immunoprecipitation sequencing (MeDIP-seq). We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The methylation levels varied among genic regions (Table 1) and the promoter showed the highest methylation ratio in all contexts. Our result is consistent with other species, including rice (Zhang et al, 2018a), chickpea (Bhatia, Khemka, Jain, & Garg, 2018b), lotus (Lin et al, 2019) and black poplar (Ding et al, 2018) where promoter regions were the most heavily methylated as compared to the other genic regions. In contrast, promoter regions are barely methylated in Arabidopsis (Zhang et al, 2006).…”
Section: F I G U R Esupporting
confidence: 92%
“…The methylation levels varied among genic regions (Table 1) and the promoter showed the highest methylation ratio in all contexts. Our result is consistent with other species, including rice (Zhang et al, 2018a), chickpea (Bhatia, Khemka, Jain, & Garg, 2018b), lotus (Lin et al, 2019) and black poplar (Ding et al, 2018) where promoter regions were the most heavily methylated as compared to the other genic regions. In contrast, promoter regions are barely methylated in Arabidopsis (Zhang et al, 2006).…”
Section: F I G U R Esupporting
confidence: 92%
“…A study on rice (Oryza sativa L.) found that the relative level of DNA methylation in diploid fish was higher than that in haploid fish. The methylation in CG sequence context did not differ between haploid and diploid fish [28]. In animals, DNA methylation occurs in the CG context, and it commonly occurs within all sequence contexts (CG, CHG and CHH) in plants [29].…”
Section: Discussionmentioning
confidence: 84%
“…e . the DNA methylation [ 9 ]. In plants, this modification occurs in three sequence contexts: CpG, CpHpG and CpHpH (where H = A, T or C).…”
Section: Introductionmentioning
confidence: 99%
“…It is usually assumed that DNA methylation in the gene promoter and first exon leads to the reduction in gene expression [ 10 , 11 ]. Numerous properties of the plant genome such as, its morphology, stability, differentiation, gene expression, transposable elements (TEs) transposition, chromatin structure and genome protection against mutational changes were reported to be affected by methylation [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation